2006
DOI: 10.1111/j.1600-079x.2006.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term morphological and functional evaluation of the neuroprotective effects of post‐ischemic treatment with melatonin in rats

Abstract: Consensus on neuroprotection has pointed out the relevance of the long-term morphological and functional evaluation of the effectiveness of putative neuroprotective procedures. In the present study, place learning (Morris water maze) and working memory (eight-arm Olton radial maze) were evaluated in adult male rats 90 days after 15 min of global cerebral ischemia (four-vessel occlusion) followed by continuous i.v. infusion (10 mg/kg/hr) of melatonin (Isch + Mel) or vehicle (Isch + Veh) for 6 hr, and the pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 53 publications
(99 reference statements)
6
26
1
Order By: Relevance
“…death in the hippocampus 5 days after ischemia/reperfusion. This result was supported by previous studies that melatonin protects brain damage from the ischemic damage in rats [30,31,[41][42][43][44] and gerbils [29].…”
Section: Discussionsupporting
confidence: 86%
“…death in the hippocampus 5 days after ischemia/reperfusion. This result was supported by previous studies that melatonin protects brain damage from the ischemic damage in rats [30,31,[41][42][43][44] and gerbils [29].…”
Section: Discussionsupporting
confidence: 86%
“…# Corresponding author, E-mail: duanqhwz@hotmail.com * This project was supported by a grant from the PhD Programs Experimental data from numerous studies clearly showed that melatonin, a biogenic amine produced by the pineal gland, is a highly effective agent in reducing neuronal loss and neurophysiologic deficits associated with brain ischemia and reperfusion (I/R) both in animal models and at cell level [7][8][9][10][11][12] . Yet the real mechanism for this neuronal protection is not fully elucidated.…”
mentioning
confidence: 99%
“…Methylene blue Wiklund et al, 2007. Melatonin Cervantes et al, 2008Cho et al, 1997;El-Abhar et al, 2002;García-Chávez et al, 2008;González-Burgos et al, 2007;Letechipía-Vallejo et al, 2001;Letechipía-Vallejo et al, 2007;Rennie et al, 2008;Weil et al, 2009. Other Bashkatova et al, 2001Fang et al, 2010;Gaur & Kumar, 2010;Nanri et al, 1998;Pazos et al, 1999;Sinha et al, 2001;Warner et al, 2004.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Thus, pyramidal neuron population in the Ammon´s horn of the hippocampus and in the neocortex (Bleayert et al, 1978;Colbourne & Corbett, 1994;García-Chávez et al, 2008;Hartman et al, 2005;Johansen & Diemer, 1991;Kirino, 1982;Letechipía-Vallejo et al, 2007;Moralí et al, 2011b;Pulsinelli, 1985;Schmidt-Kastner & Freund, 1991;, or different neuron types in other brain vulnerable structures (Block & Schwartz, 1998;Cervantes et al, 2002), have been evaluated through the number and proportion of surviving neurons. However, most of these studies deal with histopathological assessment of the hippocampus, the highest vulnerable brain region to global cerebral ischemia.…”
Section: Histopathological Assessmentmentioning
confidence: 99%